PENINGKATAN KEMAMPUAN MENULIS PUISI MENGGUNAKAN PENDEKATAN KETERAMPILAN PROSES DENGAN MEDIA GAMBAR PADA SISWA KELAS V SD NEGERI 4 GELATA KECAMATAN SOKAN - Madarudin Madarudin; Clarry Sada; Burhan Burhan (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to improve the student ability in writing poem by using the picture as part of approaching process. This research was an action research that includes 2 cycles, where every cycle includes: planning, implementation, observation, and reflection. The subject of this research was the 34 students of grade V Public Elementary School No.4, Gelata, Sokan District; Academic Year 2011/2012. The first cycle showed that from 25 students, there were: 26.47% or 9 students who were absent; 29.41% or 10 students, who got the grade under average 6, and 41.11% or 15 students got the grade on the average or 6). In the other hand, the second cycle showed that from 29 students, there are: 17.64% or 6 students, who were absent; 14.75% or 5 students who got the grade under the average; and 23 students who got the grade on or higher than average. Keywords: Writing Skill, Poem, Approaching on the Skill Process, Picture Media